Employer Brand and Employee Engagement as Predictors of Turnover Intention in the Hospitality Industry - Wulanmeiaya Wowor; Dedi Purwana; Thomas Suyatno (Jurnal Mantik, 2022)
The purpose of this study was to analyze: (1) the effect of employer brand on turnover intention in hotel industry; (2) the effect of employer brand on turnover intention in hotel industry; (3) the effect of employee engagement on turnover intention in hotel industry; (4) the effect of employer brand on turnover intention through employee engagement in hotel industry. The populations in this study were employees of five-star hotels in Jakarta, with a sample of 330 people. The sample technique used was simple random sampling. Data collection was done by distributing questionnaires to respondents. This study uses Structural Equation Modeling (SEM) procedures in processing data and testing the research model. The results showed that employer brand and employee engagement had a significant negative effect on turnover intention. Another result is that employee engagement significantly mediates the effect of employer brand on turnover intention. This study found that the greatest factor affecting the turnover intention of five-star hotel employees was employer brand through employee engagement. Therefore, in order to reduce turnover intention, hotels need to increase employee engagement by strengthening hotel brand employers.